Terrace gardening for healthy living - Singh, P K (Indian Horticulture, 2019)
With the help of Dr P K Singh, Ms Tara Safir has been growing vegetables, as well as herbs in pots and grow-bags. Herbs like tulsi, sweet basil, coriander, methi, mint, curry leaf, lemon balm, giloi, green chilli, elaichi, peeplie are grown throughout the year while vegetable, spinach, water spinach, tomatoes, cherry tomatoes, broccoli, kale, Pakchoi, amaramth (purple and green), bitter gourd, sponge gourd, red cabbage, green cabbage, capsicum, okra, brinjal (white, green and purple), beans, salads like romaine ettuce, rocket leaves, aragula, poi ka saag, beet roots are successfully grown in their season using soil and soil less medium with little modifications. Ms Safir enjoy sharing these freshly harvested vegetables of rooftop with her neighbours, family and friends. People feel motivated and this year her neighbours are also planning to have their own nutritional garden.